Development, relative validity, and reliability of a food frequency questionnaire for a case-control study on dietary advanced glycation end products and diabetes complications. (22nd July 2013) - Luevano-Contreras, Claudia; Durkin, Taylor; Pauls, Maria; Chapman-Novakofski, Karen
Abstract: Dietary advanced glycation end products (dAGEs) could be involved on diabetes complications, yet their quantification is not standardized. The objective of this study was to design a food frequency questionnaire (FFQ) for dAGEs, and to assess its reliability and validity. For the design, data from 30 subjects was used. The final instrument had 90 food items. To measure reliability and validity, 20 participants with type 2 diabetes filled out twice the FFQ (FFQ-T1, FFQ-T2) and 7-day food records (7-dFR). The Shrout–Fleiss coefficient was 0.98 showing good reliability. For validation, the results for the weighted kappa were 0.55 (moderate agreement) for FFQ-T1 and 0.64 (good agreement) for FFQ-T2, and 75% and 80% of subjects respectively were correctly classified into tertiles; Bland–Altman graphics showed no systematic bias. This FFQ is comparable to 7-dFR for measuring dAGEs. To our knowledge, this is the first questionnaire designed to measure specifically dAGEs.